English through Music: Designing CLIL materials for young learners (Journal of Parents and Teachers, 2013)
Jane Willis offers guidelines for developing a CLIL course for non-music specialist primary teachers of English as a second or foreign language. Drawing on lively activities from music education materials from the UK, she describes how she and a music specialist co-operated to design a music syllabus and integrate a language component. They selected activities that were popular amongst music teachers and recorded them being taught in English in local schools by primary and early secondary teachers.  They then analysed the classroom language used in the lessons and from this derived a language syllabus to complement the music syllabus and design a Music course.
Keywords: Music activities; language learning; CLIL; syllabus design